2015
DOI: 10.1371/journal.pone.0143849
|View full text |Cite
|
Sign up to set email alerts
|

Natural Scaffolds for Renal Differentiation of Human Embryonic Stem Cells for Kidney Tissue Engineering

Abstract: Despite the enthusiasm for bioengineering of functional renal tissues for transplantation, many obstacles remain before the potential of this technology can be realized in a clinical setting. Viable tissue engineering strategies for the kidney require identification of the necessary cell populations, efficient scaffolds, and the 3D culture conditions to develop and support the unique architecture and physiological function of this vital organ. Our studies have previously demonstrated that decellularized sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…were the first group to show the proliferation and differentiation capacity of these cells in a kidney scaffold. The Batchelder group reported similar observations . Bonandrini et al .…”
Section: Kidneysupporting
confidence: 53%
See 1 more Smart Citation
“…were the first group to show the proliferation and differentiation capacity of these cells in a kidney scaffold. The Batchelder group reported similar observations . Bonandrini et al .…”
Section: Kidneysupporting
confidence: 53%
“…The cells used for recellularization need guidance for their rearrangement and maturation, a task that is better performed by the ECM and its residual components. Indeed, as mentioned above, the preservation of the organ‐specific ECM components such as growth factors and various structural proteins facilitates an optimal recellularization process . However, an organ might be reconstructed by cultivating organ‐specific cells in an ECM derived from another organ (e.g.…”
Section: Recellularizationmentioning
confidence: 99%
“…According to increased expression of surface markers, ESCs were induced to differentiate into kidney progenitors. Besides, hESCs were seeded onto renal ECM microscaffolds and cultured with sequential application of growth factors, which further confirmed the differentiation potential of ESCs into renal cells (Batchelder, Martinez, & Tarantal, ). Additionally, Song et al established a double cell perfusion system into complete decellularized kidney matrix: Human umbilical vein endothelial cells were perfused through renal artery, and rat neonatal kidney epithelial cells were reversely perfused via urinary tract so that both vascular structure and renal tubular can be produced.…”
Section: Application Of Construction Strategies In Solid Organ Tissuementioning
confidence: 53%
“…We also found that decellularization through both PR could effectively remove cell content, and the ECM structure was preserved, and microscopic examination showed that the ECaM fibers were not only present but that the ultrastructure and 3D‐organization were preserved well. Conservation of the 3D‐ECM ultrastructure can facilitate cell adhesion, survival, and integration . This technique without using any enzymatic degradations also could significantly reduce the time of production and better preserve scaffold architecture and ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…Conservation of the 3D-ECM ultrastructure can facilitate cell adhesion, survival, and integration. 26,27 This technique without using any enzymatic degradations also could significantly reduce the time of production and better preserve scaffold architecture and ECM components.…”
Section: Discussionmentioning
confidence: 99%